Blood Milieu in Acute Myocardial Infarction Reprograms Human Macrophages for Trauma Repair. Issue 5 (16th December 2022) - Fontaine, Margaux A. C.; Jin, Han; Gagliardi, Mick; Rousch, Mat; Wijnands, Erwin; Stoll, Monika; Li, Xiaofei; Schurgers, Leon; Reutelingsperger, Chris; Schalkwijk, Casper; van den Akker, Nynke M. S.; Molin, Daniel G.M.; et al.
Abstract: Acute myocardial infarction (AMI) is accompanied by a systemic trauma response that impacts the whole body, including blood. This study addresses whether macrophages, key players in trauma repair, sense and respond to these changes. For this, healthy human monocyte‐derived macrophages are exposed to 20% human AMI ( n = 50) or control ( n = 20) serum and analyzed by transcriptional and multiparameter functional screening followed by network‐guided data interpretation and drug repurposing. Results are validated in an independent cohort at functional level ( n = 47 AMI, n = 25 control) and in a public dataset. AMI serum exposure results in an overt AMI signature, enriched in debris cleaning, mitosis, and immune pathways. Moreover, gene networks associated with AMI and with poor clinical prognosis in AMI are identified. Network‐guided drug screening on the latter unveils prostaglandin E2 (PGE2) signaling as target for clinical intervention in detrimental macrophage imprinting during AMI trauma healing. The results demonstrate pronounced context‐induced macrophage reprogramming by the AMI systemic environment, to a degree decisive for patient prognosis. This offers new opportunities for targeted intervention and optimized cardiovascular disease risk management. Abstract : A heart infarct induces profound changes to blood composition, which may impact key cells in repair of the heart after infarction: the macrophages. Here, this work demonstrates that macrophages are reprogrammed by their exposure to blood from infarcted patients. This has consequences for the patients' future cardiovascular health but also offers new opportunities for therapeutic intervention.